Analisis Batuan Berdasarkan Petrografi Daerah Mehanggin dan Sekitarnya, Kabupaten OKU Selatan, Sumatera Selatan - Ananda Giselle Putri Ianuar; Idarwati (Mataram University, 2025)
This study aims to assess the petrological and petrographic characteristics of the Mehanggin area and its surroundings, South Ogan Komering Ulu (OKU) Regency, South Sumatra. The research site covers an area of ±27 km² with lithological complexity in the form of igneous, pyroclastic, sedimentary and metamorphic rocks. The methods used include surface geological mapping, megascopic petrological analysis, and petrographic analysis using thin sections with a polarizing microscope. The results showed the presence of ten lithostratigraphic units, namely Phyllite, Andesite, Chert, Granite, Conglomerate, Sandstone, Limestone, Carbonate Sandstone, Clay, and Tuff. Further petrographic analysis identified each unit as Semipelite (Phyllite), Andesite, Chert, Monzo-granite, Arkose, Subarkose, Framestone, Unsorted Biosparite, Mudrock, and Vitric Tuff. These findings reflect the diversity of lithologies and geological processes that shaped the study area, while contributing to the understanding of the geological evolution of the South Sumatra Basin.